Desenvolvimento de recurso digital acessível para a alfabetização de estudantes com necessidades complexas de comunicação - Avelan, Danielly (Universidade Federal de São Carlos, 2025)
This research focused on the development of a digital resource aimed at the literacy of students with Complex Communication Needs (CCN). Based on the principles of Augmentative and Alternative Communication (AAC) and Assistive Technology (AT), the study sought to understand how accessible digital resources can contribute to the inclusion of students who present limitations in the communicative domain, promoting language development and their entry into the world of reading and writing. The general objective was to develop a digital pedagogical resource to support the literacy process of children with CCN, with a particular focus on the development of phonological awareness. Its design was grounded in AAC principles and included the use of pictograms from the Aragonese Center of Augmentative and Alternative Communication (ARASAAC). The methodology adopted was qualitative and applied in nature, involving bibliographic research and the development of the educational product, which was evaluated by 15 educators through an online questionnaire. Responses were collected between September and October 2025 and subsequently analyzed using content analysis as proposed by Bardin (2016). Based on Instructional Design (ID), the multi-format digital book *“The Parrot Alfredo’s Backpack”* was developed. The study results indicated that the resource is applicable in fostering predictive literacy skills, enabling the integration of pedagogical and technological principles in support of inclusion. The development of the resource highlighted the importance of understanding AAC as a mediating tool in the process of acquiring reading and writing skills. It is concluded that the digital book produced has pedagogical and inclusive potential, contributing to the expansion of access while considering the specific needs of the target group of children. However, the need for future validation stages in real contexts is emphasized, in order to more thoroughly assess its limitations and possibilities. The study demonstrates that the development of digital resources from the perspective of AT and AAC is a viable and necessary path to ensure the right to communication and literacy for all students.
Development of an accessible digital resource for the literacy of students with complex communication needs
Keywords: Necessidades complexas de comunicação; Tecnologia assistiva; Comunicação alternativa e ampliada; Alfabetização; CIENCIAS HUMANAS::EDUCACAO; 4. Educação de Qualidade